2014
DOI: 10.1002/jssc.201300894
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a PEG/hydroxypropyl starch aqueous two‐phase system for the separation of monoclonal antibodies from cell culture supernatant

Abstract: In this study, an aqueous two-phase system (ATPS) with PEG and hydroxypropyl starch (HPS) was used to separate monoclonal antibody (mAb) from Chinese hamster ovary cell culture supernatant. The phase diagram of the PEG/HPS ATPS was determined, and the effects of NaCl addition were investigated. The results showed that NaCl addition could lead to a shift of the binodal curve and that phase separation would occur at higher PEG and HPS concentrations. The effects of NaCl addition, pH, and the load of cell superna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…ATPSs have been long explored as a unique and efficient extraction pipeline, which offers a single-step procedure for the separation, recovery, purification, and enrichment of biomolecules such as enzymes, cells, particles [35], peptides, proteins [36][37][38][39][40][41], antibodies [42,43], pigments [44][45][46][47], algae-derived bioproducts [48], and natural products [49][50][51][52][53].…”
Section: Aqueous Two-phase Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATPSs have been long explored as a unique and efficient extraction pipeline, which offers a single-step procedure for the separation, recovery, purification, and enrichment of biomolecules such as enzymes, cells, particles [35], peptides, proteins [36][37][38][39][40][41], antibodies [42,43], pigments [44][45][46][47], algae-derived bioproducts [48], and natural products [49][50][51][52][53].…”
Section: Aqueous Two-phase Systemsmentioning
confidence: 99%
“…Aqueous two‐phase extraction (ATPE), which based on ATPSs, is a promising downstream processing technology in biotechnological industry and it has developed as new prospects in biomedical applications [13, 33, 34]. ATPSs have been long explored as a unique and efficient extraction pipeline, which offers a single‐step procedure for the separation, recovery, purification, and enrichment of biomolecules such as enzymes, cells, particles [35], peptides, proteins [36–41], antibodies [42, 43], pigments [44–47], algae‐derived bioproducts [48], and natural products [49–53].…”
Section: Aqueous Two‐phase Systemsmentioning
confidence: 99%
“…The authors found that the use of the ATPS protocol was highly useful for initial protein recovery and partial purification of mAb before proceeding to Protein-A affinity chromatography. Wu et al 103 reported the use of ATPS for the purification of mAbs in cell culture supernatant. The authors found that using the salt/ polymer method of ATPS (which involved increasing the concentration of NaCl) caused the formation of IgG precipitants, an undesirable end product contaminant.…”
Section: Aqueous Two-phase Partitioningmentioning
confidence: 99%
“…101,103,104 Cao et al 104 investigated the purification of monoclonal anti-clenbuterol (CL) antibody using ATPS with differing PEG concentrations, pH values, and NaCl concentrations. Optimum conditions achieved antibody recovery yields of 87.86%.…”
Section: Aqueous Two-phase Partitioningmentioning
confidence: 99%
“…ey have mild separation conditions, rapid balance processes, and high rate of product recovery. As a "green chemistry," ATPS now is widely used in the separation of protein [6,7], DNA [8], drugs [9], antibiotic [10,11], and metal ion [12]. So, we pay more attention to find a new ATPS to extract vitamin B 6 .…”
Section: Introductionmentioning
confidence: 99%